Bernard Williams and the Basic Legitimation Demand: A Defence. (13th September 2013) - Hall, Edward
<x xml:space="preserve">Abstract</x> In this article I discuss Bernard Williams' realist conception of legitimacy. According to his critics Williams tacitly incorporates various moral claims, endorses a philosophically suspect 'consensus' view of politics, and employs an unrealistic and moralised conception of political rule. I argue that these criticisms mischaracterise the nature of the basic legitimation demand and the judgements about the acceptability of the state at its core and conclude that political theorists who object to the direction and style of much contemporary political theory should take seriously the possibility of developing an appropriately 'political' political theory on Williamsian lines.